Changes in forest structure, fuels and potential fire behaviour since 1873 in the Lake Tahoe Basin, USA. Issue 1 (7th June 2013) - Taylor, Alan H.; Vandervlugt, Anna M.; Maxwell, R. Stockton; Beaty, Robert M.; Airey, Catherine; Skinner, Carl N.; Woods, Kerry
Abstract Questions What were the characteristics of pre‐Anglo‐American (reference) forests before logging, grazing and fire exclusion, and how have they changed? What were the structural characteristics of canopy and surface fuels and potential fire behaviour in reference forests, and how do they compare to contemporary forests? How might information from reference conditions be used to inform current restoration and management practices? Location Lake Tahoe Basin in the Sierra Nevada, California and Nevada, USA. Methods Tree species composition, size structure, basal area, density, surface and canopy fuels, and potential fire behaviour were quantified for reference and contemporary conditions in 32 stands. This was accomplished by integrating field measurements and dendroecological techniques with vegetation and fire behaviour simulation models. Results Contemporary Jeffrey pine and mixed conifer forests had more trees, more basal area, smaller trees and a different size structure than the reference forest. Contemporary red fir and lodgepole pine forests also had more and smaller trees, but basal areas were similar to the reference. Red fir forests also shifted in composition towards lodgepole pine. Vegetation and fire models indicate that contemporary Jeffrey pine and mixed conifer forests have higher flame length, rates of spread, lower crowning and torching indices, and more passive crown fire than the reference forests. In contrast, contemporary red fir and lodgepole pine forests only had lower crowning and torching indices, and flame length and rate of spread were only higher with extreme weather and high surface fuel load. Conclusions Contemporary Jeffrey pine and mixed conifer forests deviate the most from the reference, and restoration objectives for these forests should emphasize density and basal area reduction of smaller diameter stems. Restoration objectives for red fir should shift species composition and reduce basal area by thinning smaller diameter lodgepole pine. For lodgepole pine forests, restoration objectives should include reduction of density and basal area of smaller diameter stems. Fire or other surface fuel treatments will be needed in all the forests to maintain lower fuel loads, albeit at different time intervals.